Joule-Thomson Inversion Curves Calculation by Using Equation of State - Haghighi, Behzad; Reza Bozorgmehr, Mohammad (Asian Journal of Chemistry, 2011)
Since the prediction of the Joule-Thomson inversion curve is known as a sever test of the equations of state (EoS). Some cubic equations of state (CEoS) can eventually have inadequate prediction for checking their ability to calculate the Joule-Thomson inversion curve. In this paper the Joule-Thomson inversion curve has been used to test the predictive capabilities of some recent equations of state. This enables us to judge the accuracy of the results obtained from different equations of state. These five equations of state are: Wang-Gmehling (WG) equations of state, modified Peng-Robinson by Twu-Coon-Cunningham (PR-TCC) equations of state, Riazi- Mansoori (RM) equations of state, Geana equations of state and modified Peng-Robinson-Stryjek- Vera proposed by Samir I. Abu-Eishah (PRSV2) equations of state. All of these equations of state are modified van der Waals (vdW) equations of state recommended in the literature for estimating volumetric properties of relevant compounds. As a corollary to the present study, we have perceived that the investigated equations of state give good prediction of the low-temperature branch of the inversion curve, except for Riazi-Mansoori and Geana equations of state. We also calculated maximum inversion temperature and maximum inversion pressure for every component used in this work.